PEMBERDAYAAN PEREMPUAN MELALUI PEMANFAATAN LAHAN PEKARANGAN SEBAGAI UPAYA KETAHANAN PANGAN MANDIRI DI MASA PANDEMI COVID-19 - Mahmudah, Nurul; Al Kautsar, Muhammad Syakir (Jurnal Studi Gender dan Anak, 2021)
Abstrak: Community service is a means for empowerer to contribute to society. In the face of the pandemic, all sectors are affected, one of which is the agricultural sector. Demanding the community to reduce activities outside the home, especially women. Optimizing home gardens as a source of family food is one of the best options, especially when some areas are predicted to experience a food crisis that has the potential to affect food production. Facing a pandemic condition, the community must be able to provide food and produce it themselves. Sidomulyo Village, Punggur District, Central Lampung Regency. is a lowland area with low land use as agricultural land. It is hoped that the use of yard land as food land can help household communities meet the adequacy of food during the Covid 19 pandemic. People can grow food crops, including: sweet potatoes, cassava, vegetables, taro and other horticultural crops. This encourages them to carry out outreach activities to women about optimizing yard land as source of food in the face of the Covid-19 pandemic.